Game user experience and player-centered design (Springer, 2020)
This book aims to provide a comprehensive coverage of the basic components of game user experience and the fundamentals of player-centered design. The impact of game user experience on the game development cycles, as well as its impact on the entertainment and the educational value of a game will be covered with research findings and industry case studies. The evolution of game user experience in the new era of VR and AR will also be demonstrated. And finally, evaluations and validations of the different techniques for measuring game user experience will be followed by descriptions of how these measurements can be applied to a player-centered design.